2017
DOI: 10.1186/s40249-017-0277-3
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Toxoplasma gondii in chicken and soil of chicken farms in Nanjing region, China

Abstract: BackgroundSoil is increasingly recognized as an important source in the transmission of Toxoplasma gondii (T. gondii). The aim of this study was to investigate the presence of T. gondii in the soil and to grasp the relationships between the contamination of soil and chicken infections.MethodsPCR method based on T. gondii-conserved gene internal transcribed spacer 1 (ITS-1) as target gene and ELISA method (sGRA8-ELISA) using the recombinant protein of shortened GRA8 gene of T. gondii as antigen were developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 35 publications
3
19
1
1
Order By: Relevance
“…The seroprevalence was highest in samples collected in autumn, suggesting that fresh grass used as cattle food may harbor T. gondii oocysts, and a humid environment favors the survival of oocysts in this season. The results of the present study agree with those of previous reports [ 29 31 ]. However, some studies have shown that season is not a risk factor for T. gondii infection [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…The seroprevalence was highest in samples collected in autumn, suggesting that fresh grass used as cattle food may harbor T. gondii oocysts, and a humid environment favors the survival of oocysts in this season. The results of the present study agree with those of previous reports [ 29 31 ]. However, some studies have shown that season is not a risk factor for T. gondii infection [ 32 , 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…According to the effect of seasons on infection with T. gondii, Autumn was recorded the highest rate of infection with significant difference, the present study consistent with the study (22) in China where they revealed that T. gondii was found in 6 (3.33%) samples collected in Autumn and 1 (0.56%) collected in winter, this indicated that seasons might have important impacts on the presence of T. gondii, likewise (23) recorded rising in infection rate during winter and spring than Autumn and summer and referred to that seasonal variation of T. gondii infection in human are remarkably different than animals, also seasonal variation study on pregnant women in France appeared that the maximal risk of infection between end of summer to end of Autumn (24). this may be related to the availability of favorable conditions for oocysts maturation and sporulation to become infective (25).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, humid environment exist in these seasons may favor the survival of T. gondii oocysts. Our findings were similar to results of previously published works [53,62,63]. Though, some surveys have exposed negative portion of season for incidence of T. gondii [64,65].Previous work [66] described that 85 out of 3531 (2.41%) samples collected through autumn seasons were positive for T. gondii.…”
Section: Discussionsupporting
confidence: 92%